Bahtsul Masail sebagai Problem Solving Method dalam Pembelajaran Fikih Kontekstual - Zaenal Arifin; Chothibul Muttaqin (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
This article intends to photograph the implementation of Bahtsul Masail LBM HM Al-Mahrusiyah Putra and relate it to problem solving methods. This forum is an effort so that the students are able to contextualize the understanding they get from the yellow book into actual problems and try to describe and trace the basis of the arguments that have been used by previous scholars in formulating a law. The focus of this research is; 1) how the practice of bahtsul masail as a problem solving method in the learning of contextual Jurisprudence in LBM HM Al-Mahrusiyah Putra, 2) how do the students respond to the practice of bahtsul masail as a problem solving method in contextual learning in LBM HM Al-Mahrusiyah Putra. With a qualitative descriptive approach, data collection using interview, observation, documentation and questionnaire techniques, obtained results; bahtsul masail at LBM HM Al-Mahrusiyah Putra was good enough. The method used in the forum is broadly the same as the problem solving method. Santri who actively participated in bahtsul masail showed a positive response to the implementation of the forum. Whereas the less active santri showed a passive response and their interest tended to diminish.